Implementation of Learning Management Model of Character Education in Early Childhood in Tarbiyatul-Athfal (TA) Semarang - Nurussa'adah, Nurussa'adah (Universitas Negeri Semarang, 2014)
Learning activities within the framework of character development that learners can use as a contextual approach to teaching and learning concepts and help students advance of the material that is taught to associate with real-world situations so that learners are able to make connections knowledge with applicability in their lives. so, through contextual learning more learners have comprehensive results not only on the cognitive level (though the thought), but at the level of affection (heart, though, taste, and intention) and psychomotor (sports).Â This study intends to examine the implementation of the model of Learning Management Character Education in Early Childhood in TA as the city of Semarang and a pilot study in roommates researchers stacking dissertation will be titled character education management patterns in early childhood the TA as the city of Semarang. Formulation of the problem in this research is: how does Character Education Learning Management modeling Early Childhood in the TAas Semarang? In accordance with the formulation of the research problem, the general objectives to be achieved through this research is to find simultaneously describe the Learning Management Character Education in Early Childhood in the TA as the city of Semarang. Referring to the objectives to be achieved, this research program was designed with a